Pengaruh Penerapan Total Quality Management, Komitmen Organisasi pada Kinerja Manajerial dengan Reward sebagai Variabel Moderasi - Parwitasari, Anak Agung Sagung Istri Devi; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi, 2018)
Managerial performance becomes one of the benchmarks of a company's success. Managerial performance is an important factor in the company. The implementation of the reward system within the company will improve the quality of the manager's work within the company. The purpose of this study is to determine the effect of total quality management (TQM), organizational commitment to managerial performance moderated by the reward system. This study was conducted at 16 hospitals in Denpasar City. The number of respondents used are 55 heads of divisions which is selected using purposive sampling technique. Data collection methods were conducted by survey using questionnaire. Data analysis technique used is Moderated Regression Analysis (MRA). The final result of the study stated that the total quality management and organizational commitment have positive effect on the managerial performance, while the reward system variable strengthens the influence of total quality management and organizational commitment on managerial performance. Keywords: total quality management, organizational commitment, reward system, managerial performance.